Konstruksi Kecantikan Perempuan Pada Feature How To Do Di Kanal Beauty Fimela.Com - Siti Nawiroh; Rohmadtika Dita (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to examine the construction of women’s beauty and how existentialist feminists observe the how-to-do feature on the beauty channel Fimela.com. This article utilizes social semiotics as explained by M.A.K Halliday. The beauty construction formed by Fimela.com refers to a healthy, clean, fresh body, shining eyes, smooth clean face, free of black spots and has small pores, glowing face, no eye bags and acne scars. Beauty can be obtained in three ways: naturally, through makeup, and through instant methods. In respect of existentialist feminism, women have not yet realized their right to be free and are still objects of patriarchy. Narcissism appears in features with many women considering physical beauty important to be recognized in the public sphere. Beauty care is very important for women. This is illustrated from the discourse field: discussing beauty tips and tricks, beauty steps achieved instantly and naturally through makeup. Involvement of discourse: resource persons with domestic or international credentials who have high credibility in their fields, are intelligent, and have positive inspiration for readers. Means of discourse: there are terms of cosmetology and medical terms using semi-formal language.